Factors Involving in the Substance Abuse among Medical Students and its Association with medical students' general health: mixed-method study - Sepideh Herizchi; Ghader Dargahi Abbasabad; Parvin Delnavaz; Hojjat Torkmandi; Sina Dezhampor; Bahman Roshenas; Rahele Modaber; Mohammad Abdi (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Substance abuse has a reciprocal association with the individuals' general health; and its incidence among medical students is highly variable over time. Objectives: The present study aimed to investigate the factors involved in the substance abuse and its association with medical students' general health. Methods: The present mixed-method study was conducted on the medical students of Azad University of Tabriz in 2018 with Stratified Random Sampling. Data were collected using the General Health Questionnaire-28 (GHQ-28) and a researcher-made substance abuse questionnaire and then was analyzed through tests, chi-square, ANOVA, post hoc Howell Games and Multivariate regression models were using the SPSS16. Results: 150 medical students with a mean age of 26.98±3.46 are participating in the present study. 17.3% of students were substance abusers. The highest rate of abuse was related to Ritalin. The mean scores of the general health of addicted and non-addicted students were 42.65±11.95 and 23.62±16.83 respectively, and it was statistically significant (p= 0.012). Academic pressure was the main reason for Substance Abuse. Anxiety and insomnia were the most essential predictors decreasing general health among students with substance abuse. Conclusion: The prevalence of substance abuse among medical students was unexpected. Medical students are at risk of addiction due to the inadequate distribution of academic pressure and other predisposing factors. The implementation of practical strategies in training environments, families, and society is very important to prevent and improve the current status.